2018
DOI: 10.1021/acsomega.7b01922
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the Electrochemical Performance of Li1.2Mn0.54Ni0.13Co0.13O2 by Atomic Layer-Deposited CeO2 Coating

Abstract: It has been demonstrated that atomic layer deposition (ALD) provides an initially safeguarding, uniform ultrathin film of controllable thickness for lithium-ion battery electrodes. In this work, CeO 2 thin films were deposited to modify the surface of lithium-rich Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O 2 (LRNMC) particles via ALD. The film thicknesses were measured by transmission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…The n‐LMR/Ce cathode shows a discharge capacity of 161.3 mAh g −1 and capacity retention of 84.6 % after 100 cycles. This illustrates that the CeO 2 coating layer is useful for improving the cathode stability, which may be ascribed to the protective CeO 2 layer mitigating oxygen release from the surface and suppressing side reactions with the electrolyte compared to those during the cycling performance of the pristine n‐LMR cathode.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The n‐LMR/Ce cathode shows a discharge capacity of 161.3 mAh g −1 and capacity retention of 84.6 % after 100 cycles. This illustrates that the CeO 2 coating layer is useful for improving the cathode stability, which may be ascribed to the protective CeO 2 layer mitigating oxygen release from the surface and suppressing side reactions with the electrolyte compared to those during the cycling performance of the pristine n‐LMR cathode.…”
Section: Resultsmentioning
confidence: 99%
“…To suppress the side reactions between the electrode/electrolyte and mitigate the oxygen release from the surface of LMR materials, we use cerium oxide (CeO 2 ) to coat the micron‐ and nano‐sized LMR particles, respectively. The CeO 2 coating materials not only prevent the electrode from being directly exposed to the electrolyte but also have an oxygen storage capability that improves the surface stability of layered oxide materials during the redox reaction (CeO 2 ↔CeO 2−x +x/2O 2 ; x=0−0.5) . On the basis of these efforts, we propose a practical modification strategy by combining micron‐ and nano‐sized particle blending and CeO 2 surface coating modifications to enhance the integral performance of LMR materials, including tap density, rate capability and long‐term cycling life.…”
Section: Introductionmentioning
confidence: 99%
“…Through ALD treatment, a coating layer can be formed on LIB cathode surface, which would protect active materials against erosion from the electrolyte. Similar with the purpose of other coatings [29,63], the main function of the ALD coating layer is to separate electrolyte and active materials, inhibiting the electrolyte corroding the active material, as shown in Fig. 2(c).…”
Section: Decreasing Side Reactionsmentioning
confidence: 99%
“…Mn K-edge EELS spectral measurements (Figure 8c,d) indicated that the presence of an Al 2 O 3 surface layer suppresses dissolution of Mn ions and thus retards the consequent structural changes. There are reports on the use of ALD processes for coating LMLO materials with other oxides such as TiO 2 [137] and CeO 2 [138] and with phosphates such as AlPO 4 . [139] Similar to ALD, molecular layer deposition (MLD) adopts small and bifunctional organic molecules to build up organic or organic-inorganic hybrid materials.…”
Section: Atomic Layer Depositionmentioning
confidence: 99%